Two-dimensional diamond composite silver nanoparticle fluid lubricant as well as preparation method and application thereof
By attaching silver nanoparticles and organic canopy on two-dimensional diamond nanosheets, combining fluid lubrication and boundary lubrication, the problem of uneven contact stress at the friction interface of nanomaterials is solved, and the low friction and low wear effect between steel and ceramics is achieved .
Patent Information
- Application Number
- CN202411279036.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
Existing nanomaterials have uneven contact stress in friction interfaces, resulting in poor lubrication effect, making it difficult to meet the lubrication needs of different contact stress sites.
Using a fluid lubricant of two-dimensional diamond composite silver nanoparticles, the soft and hard multi-layer structure of bone joints is simulated by attaching silver nanoparticles to the two-dimensional diamond nanosheets and forming an organic canopy with silicone and chain organic polymers, combining the soft and hard multi-layer structure of the bone joints. Fluid lubrication and boundary lubrication adapt to the needs of different contact stress sites.
Low friction and low wear between steel and ceramics are achieved, with a coefficient of friction decreased by 93.6% and a wear decreased by 63.2%, improving the fitness and wear resistance of lubricating performance.
Smart Images

Figure CN119144372A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lubrication, and in particular relates to a fluid lubricant of two-dimensional diamond composite silver nanoparticles and a preparation method and application thereof. Background Art
[0002] The friction caused by the movement between mechanical parts will cause damage to mechanical parts and energy dissipation. This failure will cause serious harm to the machine. Lubricants are usually needed to alleviate and solve the mechanical damage caused by friction and wear. When two friction surfaces contact each other, due to the influence of the contact surface roughness, non-uniform contact is formed between the interfaces, which easily leads to uneven contact stress distribution.
[0003] Nanomaterials have good load-bearing capacity and excellent film-forming properties on friction surfaces due to their tiny size, high specific surface area, and good mechanical properties, and are often used to improve lubrication performance. However, when nanomaterials are used to improve lubrication performance, they are often affected by the uneven contact stress of the friction interface, resulting in poor lubrication effect and difficulty in meeting the lubrication effect at different contact stress sites on the friction surface. In order to pursue better lubrication performance and meet the lubrication requirements at different contact stress sites on the friction surface, it is currently urgent to prepare nanocomposites that can adapt to different contact stress conditions. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a two-dimensional diamond composite silver nanoparticle fluid lubricant and a preparation method and application thereof, so as to solve the problem in the prior art that when nanomaterials are used to improve lubrication performance, the contact stress of the friction interface is uneven, resulting in poor lubrication effect.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The first aspect of the present invention provides a two-dimensional diamond composite silver nanoparticle fluid lubricant, comprising a two-dimensional diamond nanosheet, on which silver nanoparticles are attached, and on which a chain organic polymer is grafted via organic silicon, wherein the organic silicon and the chain organic polymer constitute an organic corona.
[0007] Preferably, the organosilicon is any one of a silane coupling agent or an organosilicon quaternary ammonium salt.
[0008] Preferably, the silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane; and the organosilicon quaternary ammonium salt is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0009] Preferably, the chain organic polymer is any one of polyetheramine M2070, polyetheramine M1000, polyetheramine T5000 and polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt.
[0010] The second aspect of the present invention provides a method for preparing a fluid lubricant of two-dimensional diamond composite silver nanoparticles, the specific process is:
[0011] Dispersing the two-dimensional diamond nanosheets of composite silver nanoparticles to obtain a dispersion, heating and stirring the dispersion and the organic canopy to react and then dialyze to obtain a fluid lubricant of the two-dimensional diamond composite silver nanoparticles;
[0012] The preparation process of the two-dimensional diamond nanosheet of the composite silver nanoparticles is as follows:
[0013] Step 1, dispersing diamond nanosheets evenly in tris(hydroxymethylaminomethane) hydrochloric acid buffer, adding dopamine hydrochloride to obtain a polydopamine-coated diamond nanosheet solution, washing, filtering and drying to obtain polydopamine-coated two-dimensional diamond nanosheets;
[0014] Step 2, mixing and stirring the two-dimensional diamond nanosheets wrapped with polydopamine and the silver ammonia solution, washing and filtering the reaction product to obtain the two-dimensional diamond nanosheets composited with silver nanoparticles;
[0015] The organic canopy is a composite of organosilicon and chain organic polymer, and the preparation process is: mixing an organosilicon solution and a chain organic polymer solution, stirring and reacting to obtain the organic canopy.
[0016] Preferably, in step 1, the molar ratio of the diamond nanosheets to dopamine hydrochloride is 1:1.
[0017] Preferably, in step 2, 100 mg of two-dimensional diamond nanosheets wrapped with polydopamine and 40 mL of silver ammonia solution are mixed and stirred; the concentration of the silver ammonia solution is 2 mg / mL.
[0018] Preferably, the mixing molar ratio of the organosilicon solution to the chain organic polymer solution is 1:1, and the concentration of the organosilicon solution is 5.0 wt %.
[0019] Preferably, the dispersion and the organic canopy are heated and stirred at a temperature of 35-45° C., and the reaction time is 6-12 h.
[0020] The two-dimensional diamond composite silver nanoparticles are used as fluid lubricants for lubricating metals and ceramics.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The invention discloses a nanofluid lubricant of two-dimensional diamond composite nanoparticles, which is composed of three layers of two-dimensional diamond nanosheets, silver, and polymer molecular brushes. Silver is attached to the surface of the two-dimensional diamond nanosheets in the form of nanoparticles, and the polymer molecular brushes are connected to the functional groups such as hydroxyl groups on the surface of the two-dimensional diamond nanosheets in the form of long chains, so that the nanofluid lubricant forms a composite lubricant with polymer molecular brushes. The lubricant simulates the soft and hard lubrication structure between bone joints, and constructs a mixed lubrication mode combining fluid lubrication and boundary lubrication through a multi-layer combination of soft and hard materials, thereby achieving low friction and low wear between steel and ceramics. Among them, the two-dimensional diamond nanosheets, as a "hard" material, have inherent strength and resistance to deformation and wear. At the same time, by using soft silver particles to achieve large deformation and energy dissipation, the material has both hardness and flexibility, and improves the adaptability of the material in different environments. The polymer molecular brush composed of organosilicon and polyetheramine oligomer is grafted on the surface of the two-dimensional diamond nanosheet composite silver, thereby giving the nanocomposite material room temperature fluidity. The polymer molecular brush with active adsorption sites grafted on the surface of the two-dimensional diamond nanosheet composite silver solves the problem of poor interface bonding between the nanomaterial and the friction surface, which is conducive to the formation of a firm friction film on the surface of the friction pair by the nanomaterial, thereby reducing wear. This new type of lubricating material imitates the structure of the joint lubrication system, combines the synergistic effect of soft-hard materials and the advantages of fluid lubrication and boundary lubrication, and achieves a 93.6% reduction in friction coefficient and a 63.2% reduction in wear.
[0023] The present invention also discloses a method for preparing a nanofluid lubricant of two-dimensional diamond composite nanoparticles. The method simulates the lubrication structure of bone joints, uses two-dimensional diamond nanosheets as the core, attaches silver nanoparticles and chain-shaped organic polymer molecules thereon, and successfully prepares a nanocomposite material lubricant with the same hard-soft-soft structure.
[0024] The present invention also discloses the application of a nanofluid lubricant of two-dimensional diamond composite nanoparticles, which is a hybrid lubrication method combining fluid lubrication and boundary lubrication by combining three layers of materials, namely, two-dimensional diamond nanosheets, silver, and polymer molecular brushes; during the application process, fluid lubrication and boundary lubrication are combined, wherein the long-chain polymer molecules have the function of fluid lubrication, and boundary lubrication is achieved by the silver particles composited on the two-dimensional diamond nanosheets, and the synergistic effect between the hybrid lubrication methods is utilized to better adapt to the different stress site requirements of the friction interface. During the lubrication process, the silver nanoparticles are reduced on the surface of the two-dimensional diamond, which can dissipate energy through deformation, protect the rigid diamond from maintaining integrity during the friction process, thereby effectively reducing wear, and in particular, can meet the lubrication requirements under different contact stresses between steel and ceramics, achieve low friction and low wear, and reduce loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a perspective electron microscope image of a two-dimensional diamond nanosheet;
[0026] Figure 2 This is a high-definition transmission electron microscope lattice image of diamond composite silver nanoparticle material;
[0027] Figure 3 This is the XPS spectrum of diamond composite silver nanoparticle material;
[0028] Among them, (a) is the XPS spectra of diamond nanosheets, polydopamine-wrapped diamond nanosheets, and diamond-composite silver nanoparticles, and (b) is the XPS fitting curve of Ag 3d of diamond-composite silver nanoparticles.
[0029] Figure 4 Infrared spectra (from top to bottom: two-dimensional nanodiamond sheet, polydopamine-wrapped diamond, diamond composite silver nanoparticle material);
[0030] Figure 5 XRD diffraction patterns (from top to bottom: two-dimensional nanodiamond sheet, polydopamine-wrapped diamond, diamond composite silver nanoparticle material);
[0031] Figure 6 Raman spectra (from top to bottom: two-dimensional nanodiamond sheet, polydopamine-wrapped diamond, diamond composite silver nanoparticle material);
[0032] Figure 7 Thermogravimetric curves (from top to bottom: two-dimensional nanodiamond sheet, polydopamine-wrapped diamond, diamond composite silver nanoparticle material);
[0033] Figure 8 This is the infrared spectrum of diamond composite silver nanolubricant;
[0034] Fig. 9 It is the DSC curve diagram of diamond composite silver nano-lubricant;
[0035] Among them, (a) is a DSC curve diagram of diamond-composite silver covalent bond nanofluid, and (b) is a DSC curve diagram of diamond-composite silver ionic bond nanofluid;
[0036] Fig.10 This is the viscosity-shear rate variation trajectory of the diamond composite silver nanolubricant;
[0037] Fig.11 This is the viscosity-temperature variation trajectory of the diamond composite silver nanolubricant;
[0038] Fig.12is a friction coefficient curve of diamond composite silver nanolubricant;
[0039] Fig.13 3D contour image of diamond-composite silver nanolubricant;
[0040] Fig.14 is the wear rate bar graph of diamond composite silver nanolubricant;
[0041] Among them, (a) shows SCND@PDA@Ag-covalent bonding; (b) shows SCND@PDA@Ag-ionicbonding;
[0042] Fig.15 The friction coefficient comparison curve (from top to bottom: steel / ceramic dry friction, diamond nano-lubricant, silver nano-lubricant, diamond composite silver nano-lubricant);
[0043] Fig.16 It is a wear bar graph (from left to right: steel / ceramic dry friction, diamond nanolubricant, silver nanolubricant, diamond composite silver nanolubricant);
[0044] Fig.17 3D contour map of the wear track;
[0045] Among them, (a) shows steel / ceramic dry friction (Dry); (b) shows diamond nanolubricant (SCND-covalent bonding); (c) shows silver nanolubricant (Ag-covalent bonding); (d) shows diamond composite silver nanolubricant (SCND@PDA@Ag-covalent bonding);
[0046] Fig.18 This is the Raman spectrum of the wear track of the diamond composite silver nanolubricant;
[0047] Fig.19 FIB-TEM image of the cross section of the wear track of the diamond composite silver nanolubricant;
[0048] Fig. 20 is the transmission electron microscope image of the grinding fluid;
[0049] Among them, (a) is a diamond nanosheet; (b) is a diamond nanofluid lubricant; (c) is a diamond composite silver nanolubricant; (d) is a transmission electron microscope image of silver nanoparticles in the grinding fluid; (e) is an energy spectrum image of silver nanoparticles in the grinding fluid; (f) is a transmission electron microscope image of the deformation of silver nanoparticles in the grinding fluid. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0051] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0052] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0053] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0054] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0055] The present invention draws inspiration from nature. In nature, the multi-level structure of organisms is the result of long-term optimization of nature, especially the structure of the combination of soft and hard materials can help organisms survive in harsh environments and reduce damage caused by the outside world. It is generally believed that the synergistic effect between soft and hard materials can make full use of the inherent strength and deformation and wear resistance of hard materials, while using soft materials to achieve large deformation and energy dissipation, so that the material has both hardness and flexibility, and improves the adaptability of the material in different environments. Examples of biomaterials with this structure include animal joints, tendons, pearls, and abalone shells. Taking animal joints as an example, animal joints rely on the synergistic effect of the multilayer structure of articular cartilage, polymer boundary lubrication film and hydration layer for lubrication. The polysaccharides, proteins and lipids in the synovial fluid can recognize and bind to the cartilage surface to assemble into polymer brushes, which can adapt to different loads and friction environments on the joint surface through the adaptive synergistic effect of fluid lubrication and boundary lubrication, provide good friction performance, and protect bones from wear; inspired by the lubrication structure and mechanism of animal joints, the present invention designs and prepares a lubricant with a soft and hard multilayer structure to achieve good lubrication performance.
[0056] The present invention aims to simulate the multi-layer lubrication structure between human joints and prepare a composite nanofluid lubricant with a multi-layer structure. This new type of lubricating material imitates the structure of the joint lubrication system, combining the synergistic effect of soft-hard materials and the advantages of fluid lubrication and boundary lubrication. And it can achieve a 93.6% reduction in friction coefficient and a 63.2% reduction in wear. The present invention also studies the tribological properties of this bionic lubricant and the effects of different components on its effectiveness. In the friction process, it was unexpectedly found that the polymer in the outer layer can play a good role in dispersing silver and nanosheets. During the friction aggregation process of the dispersed nanosheets, the spherical nanosilver can convert the hard contact between diamonds into interlayer contact similar to that of layered two-dimensional materials, resulting in the stacking of diamonds into a layered structure that is easy to shear. On the one hand, the friction coefficient is reduced, and on the other hand, the friction between rigid diamonds will also release nanosilver particles, thereby further improving the lubrication performance. Diamond composite nanofluids have opened up new possibilities for the development of high-performance lubricants in the field of tribology.
[0057] Based on the above purpose, the first aspect of the present invention discloses a nanofluid lubricant of two-dimensional diamond composite silver particles, the main substance of the nanofluid lubricant is a two-dimensional diamond nanosheet, the two-dimensional diamond nanosheet is attached with silver nanoparticles, and the two-dimensional diamond nanosheet is connected with a chain organic polymer through organic silicon. The silver nanoparticles can be attached to the surface or edge of the entire two-dimensional diamond nanosheet, and the chain organic polymer forms an organic crown layer on the surface of the diamond nanosheet, which is a molecular brush structure.
[0058] The lubricant combines three layers of materials: two-dimensional diamond nanosheets, silver, and polymer molecular brushes to construct a hybrid lubrication method that combines fluid lubrication and boundary lubrication, thereby achieving low friction and low wear and reducing loss.
[0059] In some embodiments of the present invention, the organosilicon can be any one of a silane coupling agent or a quaternary ammonium salt of organosilicon; an exemplary silane coupling agent can be γ-(2,3-epoxypropoxy)propyltrimethoxysilane, referred to as KH560; the quaternary ammonium salt of organosilicon is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0060] In some embodiments of the present invention, the chain organic polymer is any one of polyetheramine M2070, polyetheramine M1000, polyetheramine T5000 and polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt, and the connection between the organosilicon and the organic polymer can be a covalent bond or an ionic bond, and the organic canopy material is prepared by matching them according to the reaction characteristics.
[0061] As a preferred solution, when the organosilicon is silane coupling agent KH560 and the chain organic polymer is oligomer polyetheramine M2070, the two are connected together by covalent bonds through an epoxy ring-opening reaction; in the presence of water, the alkoxy group of the silane coupling agent will hydrolyze to generate active silanol groups, and the silanol groups of the silane coupling agent can undergo a dehydration condensation reaction with the hydroxyl groups on the surface of the diamond to be grafted onto the diamond surface.
[0062] In some embodiments of the present invention, the thickness of the two-dimensional diamond nanosheet is 9nm. Two-dimensional nano-diamond inherits the superior properties of diamond, such as high Young's modulus, hardness, thermal conductivity, chemical stability and resistance to harsh environments, so that the two-dimensional nano-diamond thin sheet can become a solid lubricant, and lubricity and wear resistance are provided simultaneously, and the non-layered two-dimensional diamond lubrication friction is non-commensurate contact, reduces the contact area, and reduces wear. However, the rigidity itself is large, and it is difficult to provide good lubricity. Based on this, the present invention introduces silver nanoparticles on the basis of two-dimensional diamond nanosheet as a rigid matrix.
[0063] In some embodiments of the present invention, the silver nanoparticles have a particle size of 20-55 nm; the two-dimensional nanodiamond sheets simulate the hard phase structure of articular cartilage, which can provide good load-bearing and wear resistance for the silver nanomaterial particles; the silver nanoparticles can be applied to tribology due to their softness, chemical stability, low shear strength, embeddability and ductility, and can be physically pressed or applied to the contact area to form a softer and smoother nanoparticle layer, which promotes deformation and faster running-in, has greater conformal contact, and thus reduces the contact pressure of the rough surface and the shear resistance under low friction. Therefore, using silver nanoparticles to simulate the soft phase structure of articular cartilage can dissipate energy through shear deformation, and depositing metal nanoparticles on the surface of diamond nanosheets can effectively solve the problem of agglomeration between diamond nanosheets.
[0064] The second aspect of the present invention provides a method for preparing a composite silver nanoparticle diamond nanosheet lubricant simulating a bone joint lubrication structure, comprising the following steps:
[0065] The preparation method comprises the following steps:
[0066] (1) The two-dimensional diamond nanosheets were placed in a tris-hydroxymethylaminomethane hydrochloric acid buffer solution (Tris-HCl buffer, pH = 8.5) and ultrasonically dispersed uniformly, and then dopamine hydrochloride was added in a ratio of 1:1. The reaction was carried out under magnetic stirring at room temperature for 12 hours to obtain a polydopamine-coated diamond nanosheet solution.
[0067] Tris-HCl buffer solution is referred to as Tris-HCl buffer solution, which is a reaction solution. Diamond nanosheets and dopamine hydrochloride are used as reaction raw materials. The reaction mass ratio of diamond to dopamine is 1:1. The concentration of Tris-HCl buffer solution is 10mM and pH is 8.5. In an alkaline environment, dopamine hydrochloride is oxidized and self-polymerized to form polydopamine hydrochloride coated on the surface of diamond nanosheets. Polydopamine has adhesiveness because of 5,6-dihydroxyindole, and polydopamine itself has a structure similar to sticky protein, which can form a dense self-assembled film on the surface of different materials.
[0068] (2) The product obtained in step (1) is washed with anhydrous ethanol and deionized water, filtered and washed three times with a microporous filter membrane, and dried in a vacuum oven at 80° C. for 1 hour to obtain polydopamine-coated diamond nanosheets in the form of black powder; wherein the microporous filter membrane is made of organic nylon and has a pore size of 50 nanometers.
[0069] (3) Add ammonia water (concentration of 2 wt%) to the silver nitrate solution until the brown precipitate is just dissolved to prepare a silver ammonia solution.
[0070] (4) Adding the two-dimensional diamond nanosheets wrapped with polydopamine to the silver ammonia solution, the mixing ratio of the two-dimensional diamond nanosheets wrapped with polydopamine and the silver ammonia solution is: 100 mg of the diamond nanosheets wrapped with polydopamine is mixed with 40 mL of the silver ammonia solution, and vigorously stirred on a magnetic stirrer at room temperature for 24 hours. In this process, polydopamine reduces the silver ammonia complex ions in the silver ammonia solution to silver due to the reducing property of its own catechol, which is an in-situ reduction reaction, generating silver particles, and the silver particles are attached to the diamond nanosheets.
[0071] (5) The product obtained in (4) was washed with deionized water and ethanol in a vacuum filtration bottle, collected and filtered to obtain diamond nanosheets composited with silver nanoparticles.
[0072] (6) mixing an organosilicon solution and a chain organic polymer solution, wherein the organosilicon and the chain organic polymer are equimolar equivalents, and then continuously stirring the resulting mixed solution at 20-50° C. for 12-24 hours to form an organic canopy.
[0073] The organosilicon solution is a solution in which organosilicon is dissolved in ethanol, the organosilicon can be KH560, SIT or DC5700, and the concentration of the organosilicon solution is 5.0 wt %.
[0074] The chain organic polymer solution is a solution of a chain organic polymer dissolved in ethanol, the chain organic polymer is any one of polyetheramine M2070, polyetheramine M1000, polyetheramine T5000 and polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt, and the concentration of the chain organic polymer solution is 10.0wt% ethanol solution.
[0075] As a preferred solution, the organosilane KH560 ethanol solution (5.0 wt % ethanol solution) is added dropwise into the polyetheramine M2070 diluted solution (10.0 wt % ethanol solution).
[0076] (7) The diamond nanosheets of composite silver nanoparticles were uniformly dispersed in deionized water by ultrasonication, and then mixed with the product obtained in (6) at 35-45° C. and stirred for 6-12 hours. The obtained mixture was then dialyzed for 48 hours (8000MWCO dialysis bag), during which the deionized water was replaced every 4 hours to remove any excess unbound crown layer (organosilane-polyetheramine), thereby obtaining a diamond nanosheet lubricant of composite silver nanoparticles.
[0077] In the presence of water, the alkoxy groups of organic silicon such as silane coupling agent KH560 will hydrolyze to generate active silanol groups, while releasing methanol as a byproduct of the hydrolysis reaction. The silanol groups will condense with the hydroxyl groups on the surface of diamond nanosheets to form chemical bonds, and a dehydration condensation reaction will occur. Removing the unreacted organic canopy proves that this nanofluid is synthesized by chemical bond grafting, not a simple physical blend.
[0078] The microstructure of the diamond nanosheets of composite silver nanoparticles was characterized by transmission electron microscopy (TEM), Raman spectroscopy (Raman), x-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), X-ray diffraction (XRD) and other methods, and the organic matter grafting amount and other factors determined that the preparation of diamond nanosheets of composite silver nanoparticles and diamond nanosheet lubricant of composite silver nanoparticles was successful.
[0079] The tribological properties of the lubricant were tested by a UMT friction and wear tester and a 3D white light interferometer, and the results showed that the diamond nanosheet lubricant with composite silver nanoparticles prepared by simulating the bone joint lubrication system had excellent friction reduction and anti-wear properties.
[0080] The tribological mechanism of the lubricant was characterized by FIB processing, Raman, TEM, XPS and other methods. Fig.18 , 19 The Raman and FIB-TEM images show that diamond-composite silver nanomaterials were observed in the friction film in the friction track, proving that the lubricant forms a lubricating film on the wear surface during the friction process. Fig. 20 The TEM images show that the silver nanoparticles in the lubricant fall off from the diamond surface after friction, and the silver nanoparticles can be observed to have obvious lattice dislocations caused by shear force. The results show that the diamond composite silver nanolubricant can better adapt to different contact pressures through the synergistic effect of fluid lubrication and boundary lubrication. Silver nanoparticles can quickly form a soft and smooth boundary lubrication layer on the surface of diamond nanosheets, while protecting the diamond nanosheets from being easily broken, isolating the direct contact between the friction pairs and reducing friction. The shearing effect between the diamond nanosheets will also release the soft silver nanoparticles into the lubricant and deposit them in the wear grooves of the substrate, thereby achieving the effect of lubrication and repair.
[0081] In summary, a multilayer structure of diamond nanosheet lubricant with composite silver nanoparticles that simulates the lubrication structure of bone joints can effectively improve the lubrication performance between steel-ceramic pairs by combining soft and hard materials and a hybrid lubrication method that combines fluid lubrication and boundary lubrication.
[0082] The following is further described in conjunction with specific embodiments:
[0083] Example 1: Preparation of diamond-silver composite materials by simple chemical reduction
[0084] (1) Dissolve 0.606 g of Tris in 300 ml of deionized water, and add 0.5 M dilute hydrochloric acid solution dropwise with stirring to prepare a 10 mM Tris-HCl buffer solution, which is transferred to a volumetric flask with a pH of about 8.5.
[0085] (2) Disperse 0.1 g of diamond nanosheets in a Tris-HCl buffer solution and disperse them using ultrasound for 2 hours. After the diamond nanosheets are evenly dispersed, add 0.1 g of dopamine hydrochloride into the dispersed solution of the diamond nanosheets and stir to react for 10 hours. ;
[0086] (3) After the reaction is completed, the unreacted polydopamine is removed by filtration and washing with ethanol and deionized water for three times, and then dried to obtain black polydopamine-coated diamond nanosheets.
[0087] (4) Add silver ammonia aqueous solution (2 wt%) to 2 mg / mL silver nitrate solution until the brown precipitate just dissolves.
[0088] (5) 100 mg of the prepared polydopamine-coated diamond nanosheets were added to 40 ml of silver ammonia solution and vigorously stirred on a magnetic stirrer at room temperature for 24 hours. In this process, the silver ammonia solution was used as the silver precursor solution to prepare silver nanoparticles on the surface of polydopamine.
[0089] (6) The product obtained in (5) was collected and filtered in a vacuum filtration bottle by washing with deionized water and ethanol to obtain a product, a diamond-composite silver nanocomposite material.
[0090] Example 2: Preparation of diamond composite silver nanolubricant by covalent bond grafting
[0091] (1) An equimolar amount of an organosilane KH560 solution (5 wt% ethanol solution) was added dropwise to a polyetheramine M2070 diluted solution (10.0 wt% ethanol solution). The resulting mixed solution was then stirred continuously at 50°C for 12 hours to form an organic canopy. When preparing the organosilane KH560 solution, the amount of KH560 was 5 g, and when preparing the polyetheramine M2070 diluted solution, the amount of M2070 was 43.79 g.
[0092] (2) 0.3 g of diamond composite silver nanoparticle material was uniformly dispersed in 40 ml of deionized water by ultrasonication, and mixed with the mixture in step (1) at 35° C. for 6 h. The obtained mixture was then dialyzed for 48 hours (8000 MWCO dialysis bag), during which time it was renewed with DI every 4 hours to remove any excess unbound crown layer (organosilane-polyetheramine). A diamond composite silver nanolubricant prepared by covalent bond grafting was obtained.
[0093] Example 3: Preparation of diamond composite silver nanolubricant by ionic bond grafting
[0094] (1) Weigh 0.3 g of diamond composite silver nanoparticle material, disperse it in a water / ethanol (1:1) solution, and ultrasonically disperse it for 1 hour until it is uniform.
[0095] (2) Add 5 g (10 wt%) of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride in methanol to the diamond composite silver nanoparticle material dispersion. The resulting precipitate is aged at room temperature for 24 hours, shaken from time to time during this period, and then washed three times with water and methanol using a vacuum extraction bottle, and dried under vacuum at 100° C. to obtain a powder product of diamond composite silver grafted dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0096] (3) The product obtained in (2) was reacted with 10 g (10 wt%) of polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt in a chloroform solution at 70° C. for 24 hours. The reaction solution was washed with DI and ethanol by centrifugation for 3 times, and vacuum dried at 100° C. for 3 hours to obtain a diamond composite silver nanolubricant prepared by ion bond grafting, specifically dimethyloctadecyl [3- (trimethoxysilyl) propyl] ammonium chloride and polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt were grafted by ion bond.
[0097] Attached Figure 1 The TEM images show the layered structure of diamond nanomaterials. Figure 2 The TEM images show that the composite structure of diamond-polydopamine layer-silver nanoparticles can be observed in the prepared diamond-composite silver nanomaterial. Figure 3-Figure 7 It also proves that the preparation of diamond composite silver nanomaterials is successful. Figure 8 The results show that the preparation of diamond composite silver nano-lubricant by ionic bond and covalent bond grafting is successful. Fig. 9 The results show that the melting temperatures of diamond composite silver nano-lubricants prepared by ionic bond and covalent bond grafting are 12℃ and -5.65℃ respectively, and the fluidity of the lubricant can be guaranteed above this temperature. Fig.10 , 11 It shows that the viscosity of the lubricant gradually decreases with the increase of temperature and shear rate. Figure 12-14This indicates that the lubricant prepared by covalent bonds has better friction performance than the lubricant prepared by ionic bonds.
[0098] Comparative Example 1: Preparation of diamond nanolubricant by covalent bond grafting
[0099] (1) An equimolar amount of an organosilane KH560 solution (5.0 wt% ethanol solution) was added dropwise to a polyetheramine M2070 diluted solution (10.0 wt% ethanol solution), and the resulting mixed solution was stirred continuously at 50° C. for 12 hours to form an organic canopy.
[0100] (2) SCND was mixed with the mixture in step (1) at 35°C for 6 hours. The resulting mixture was then dialyzed for 48 hours (8000MWCO dialysis bag), during which it was refreshed with deionized water every 4 hours to remove any excess unbound corona (organosilane-polyetheramine). A diamond composite silver nanolubricant prepared by covalent bond grafting was obtained.
[0101] Comparative Example 2: Preparation of Silver Nanolubricant by Covalent Bond Grafting
[0102] (1) 0.068 g of silver nitrate was dissolved in 200 ml of deionized water to a concentration of 0.002 M. 0.021 g of sodium citrate was dissolved in 4 ml of deionized water to a concentration of 0.02 M and added dropwise to the silver nitrate aqueous solution, heated to boil at 150° C. for about 30 minutes. After the reaction was completed, centrifuged, washed with ethanol three times, and dried to obtain silver nanoparticle powder.
[0103] (2) An equimolar amount of an organosilane KH560 solution (5.0 wt% ethanol solution) was added dropwise to a polyetheramine M2070 diluted solution (10.0 wt% ethanol solution), and the resulting mixed solution was stirred continuously at 50° C. for 12 hours to form an organic canopy.
[0104] (3) The product of (1) was mixed with the mixture in step (2) at 35°C for 6 hours. The resulting mixture was then dialyzed for 48 hours (8000MWCO dialysis bag), during which it was refreshed with deionized water every 4 hours to remove any excess unbound corona (organosilane-polyetheramine). A diamond composite silver nanolubricant prepared by covalent bond grafting was obtained.
[0105] Figure 15-17 It shows that the friction coefficient and wear condition of the diamond composite silver nanolubricant prepared by covalent bond grafting are the best when friction tests are conducted under dry friction conditions with Comparative Examples 1 and 2 and Example 2.
[0106] Example 4
[0107] In this embodiment, the chain organic polymer is polyetheramine T5000, and the remaining parts not involved are the same as those in Embodiment 2.
[0108] Based on the above embodiments and comparative examples, it can be clearly seen that, 1. the technical solution illustrated in the embodiment of the present invention simulates the soft and hard multi-layer lubrication structure between bone joints, and prepares a diamond composite silver nanofluid lubricant composed of diamond nanosheets, silver nanoparticles, and organic canopy, which reduces the friction coefficient and wear rate between steel / silicon carbide by 93.6% and 63.2%, respectively.
[0109] 2. The multi-layer lubrication structure of diamond composite silver nanofluid lubricant combines fluid lubrication with boundary lubrication. The polymer in the outer layer can disperse silver and nanosheets very well. The silver nanoparticles on the diamond surface dissipate energy through shear deformation, thereby protecting the integrity of the diamond nanosheets.
[0110] 3. Under the action of silver nanoparticles, the spherical nanosilver can transform the hard contact between diamonds into interlayer contact similar to that of layered two-dimensional materials, causing the diamonds to be stacked into a layered structure that is easy to shear. The friction between the rigid diamonds will also release the nanosilver particles, thereby further improving the lubrication performance.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A fluid lubricant of two-dimensional diamond composite silver nanoparticles, characterized in that: The invention comprises a two-dimensional diamond nanosheet, on which silver nanoparticles are attached, and on which a chain organic polymer is grafted via organic silicon, and the organic silicon and the chain organic polymer form an organic crown layer.
2. The fluid lubricant of two-dimensional diamond composite silver nanoparticles according to claim 1, characterized in that: The organosilicon is any one of a silane coupling agent and an organosilicon quaternary ammonium salt.
3. The fluid lubricant of two-dimensional diamond composite silver nanoparticles according to claim 2, characterized in that: The silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane; and the organosilicon quaternary ammonium salt is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
4. The fluid lubricant of two-dimensional diamond composite silver nanoparticles according to claim 1, characterized in that: The chain organic polymer is any one of polyetheramine M2070, polyetheramine M1000, polyetheramine T5000 and polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt.
5. The method for preparing a fluid lubricant of two-dimensional diamond composite silver nanoparticles according to claim 1, characterized in that: The specific process is: Dispersing the two-dimensional diamond nanosheets of composite silver nanoparticles to obtain a dispersion, heating and stirring the dispersion and the organic canopy to react and then dialyze to obtain a fluid lubricant of the two-dimensional diamond composite silver nanoparticles; The preparation process of the two-dimensional diamond nanosheet of the composite silver nanoparticles is as follows: Step 1, dispersing diamond nanosheets evenly in tris(hydroxymethylaminomethane) hydrochloric acid buffer, adding dopamine hydrochloride to obtain a polydopamine-coated diamond nanosheet solution, washing, filtering and drying to obtain polydopamine-coated two-dimensional diamond nanosheets; Step 2, mixing and stirring the two-dimensional diamond nanosheets wrapped with polydopamine and the silver ammonia solution, washing and filtering the reaction product to obtain the two-dimensional diamond nanosheets composited with silver nanoparticles; The organic canopy is a composite of organosilicon and chain organic polymer, and the preparation process is: mixing an organosilicon solution and a chain organic polymer solution, stirring and reacting to obtain the organic canopy.
6. The method for preparing a fluid lubricant of two-dimensional diamond composite silver nanoparticles according to claim 5, characterized in that: In step 1, the molar ratio of the diamond nanosheets to dopamine hydrochloride is 1:
1.
7. The method for preparing a fluid lubricant of two-dimensional diamond composite silver nanoparticles according to claim 5, characterized in that: In step 2, 100 mg of two-dimensional diamond nanosheets wrapped with polydopamine and 40 mL of silver ammonia solution are mixed and stirred; the concentration of the silver ammonia solution is 2 mg / mL.
8. The method for preparing a fluid lubricant of two-dimensional diamond composite silver nanoparticles according to claim 5, characterized in that: The mixing molar ratio of the organosilicon solution to the chain organic polymer solution is 1:1, and the concentration of the organosilicon solution is 5.0 wt %.
9. The method for preparing a fluid lubricant of two-dimensional diamond composite silver nanoparticles according to claim 5, characterized in that: The heating and stirring temperature of the dispersion and the organic canopy is 35-45°C, and the reaction time is 6-12h.
10. The use of the two-dimensional diamond composite silver nanoparticles as a fluid lubricant according to claim 1, characterized in that: For lubrication of metals and ceramics.
Citation Information
Cited By
Composite nano-particle with core-chain cross-linked structure, preparation method of composite nano-particle and water-based lubricant
CN121271616A
